Clinical and molecular cytogenetic characterisation of a newly recognised microdeletion syndrome involving 2p15‐16.1 - Rajcan‐Separovic, E (BMJ Group, 2007)
BACKGROUND: During whole genome microarray‐based comparative genomic hybridisation (array CGH) screening of subjects with idiopathic intellectual disability, we identified two unrelated individuals with a similar de novo interstitial microdeletion at 2p15‐2p16.1. Both individuals share a similar clinical phenotype including moderate to severe intellectual disability, autism/autistic features, microcephaly, structural brain anomalies including cortical dysplasia/pachygyria, renal anomalies (multicystic kidney, hydronephrosis), digital camptodactyly, visual impairment, strabismus, neuromotor deficits, communication and attention impairments, and a distinctive pattern of craniofacial features. Dysmorphic craniofacial features include progressive microcephaly, flat occiput, widened inner canthal distance, small palpebral fissures, ptosis, long and straight eyelashes, broad and high nasal root extending to a widened, prominent nasal tip with elongated, smooth philtrum, rounding of the upper vermillion border and everted lower lips. METHODS: Clinical assessments, and cytogenetic, array CGH and fluorescence in situ hybridisation (FISH) analyses were performed. RESULTS: The microdeletions discovered in each individual measured 4.5 Mb and 5.7 Mb, spanning the chromosome 2p region from 57.2 to 61.7 Mb and from 56 to 61.7 Mb, respectively. Each deleted clone in this range demonstrated a dosage reduction from two to one copy in each proband except for clone RP11‐79K21, which was present in three copies in each proband and in four copies in their respective parents (two per each chromosome 2 homologue). DISCUSSION: The common constellation of features found in the two affected subjects indicates that they have a newly recognised microdeletion syndrome involving haploinsufficiency of one or more genes deleted within at least a 4.5‐Mb segment of the 2p15‐16.1 region.